Urban groundwater supplies facing dual pressures of depletion and contamination in China - Siao Sun; Hui Liu; Megan Konar; Guangtao Fu; Chuanglin Fang; Zhongwei Huang; Guagndong Li; Wei Qi; Qiuhong Tang (Proceedings of the National Academy of Sciences, 2025)
Groundwater is essential to urban water supplies throughout the world, but we do not understand how quantity and quality issues may jeopardize the ability of cities to meet their water needs. Here, we present a national analysis of both quantity and quality challenges facing China’s urban groundwater supply security, using high-resolution groundwater depletion modeling and a recently compiled dataset detailing quality violations in drinking groundwater sources. We estimate that 180 cities (about half of the prefecture-level-and-above cities), accounting for 311 million urban residents, face at least one groundwater pressure between 2016 and 2021. Cities that face dual quantity and quality pressures pinpoints hotspots of intense groundwater threats— Specifically, 40 cities, mainly situated in Northeast China and the middle to lower reaches of the Yellow River, are exposed to dual groundwater pressures. The results highlight the interconnected and possibly mutually reinforcing nature of groundwater depletion and quality issues. The logistic regression models indicate that groundwater depletion and quality violations are associated with natural water endowment and anthropogenic factors. Particularly, drinking groundwater quality issues are clustered in relation to socioeconomic gaps, with larger, wealthier cities being less prone to such problems. We argue that securing drinking water sources in small and poor cities through integrated groundwater management and economic assistance should be an important national priority for achieving groundwater supply sustainability.